Sosialisasi Dampak Bahaya Penyalahgunaan Narkotika Kepada Pelajar di SMP Negeri 4 Sesulu, Kecamatan Waru, Penajam Paser Utara - Kurnia, Wahyu Ismail; Maulana, Prethi Yunishia; Rinto; Wagimin; Sugiono, Nana (LPPM UMRI, 2023)
The purpose of the socialization activities held is to provide education, understand and reminder of insight to students about the impacts and dangers that can arise from drug abuse based on a review of legal, health, economic, social and community aspects. This activity was carried out at SMP Negeri 4 Sesulu, Kecematan Waru, Penajam Paser Utara (PPU) Regency on July 31, 2023. The participants who participated in this activity amounted to 40 people, consisting of students, teachers of SMP Negeri 4 Sesulu and representatives from the Sesulu Police Station. The method applied to this activity is by lecture techniques, and question-and-answer (discussion). Through this activity, it is expected to provide a comprehensive increase in understand and insight into the impacts and dangers that can be caused by drug abuse to students from legal, health, economic, social and community aspects as well as the negative impacts caused to the future of Indonesia's young generation.